KARAKTERISASI SIFAT MEKANIK DAN STRUKTUR MIKRO BAJA CARBON RENDAH UNTUK CANE CUTTER BLADE PADA PT GUNUNG MADU PLANTATION - Bayu Agung Permana; Mohammad Badaruddin; . Zulhanif (Jurnal Ilmiah Teknik Mesin, 2013)
Cane cutter blade (blade chopper cane), which is a tool used for chopping cane. This tool acts as a cane crusher, made of low steel carbon. Constraints that occur on Cane Cutter Blade is a high wear rate, thus disrupting the productivity of the industry. The company handles this problem by providing a coating on a cane cutter blade, only in this way is still considered very less effective at. low steel carbon relatively low carbon steel.Characterization of the mechanical properties and the microstructure of low steel carbon with hardness testing and tensile testing, while the micro picture of choice to see the results of the condition of the microstructure after a heat treatment with water as cooling media.Keywords: microstructure, cane cutter blade, low steel carbol, tensile testing, hardness testing, heat treatment.